Islam as a Theory of International Relations: A New Perspective - Bashir, Aliyu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Within the discipline of International Relations, there is a growing debate with regards to the comprehensive nature of the discipline. Non-western Scholars such as Amitav Acharya asserted that the discipline of International Relations fails to put into consideration other theories that are non-western. This, they believed, limits the discipline‟s comprehensiveness. The dominant mainstream theories are lacking in explaining complex issues around the globe that are non-western. This is because the theories are based on the euro-American worldview. Concepts such as state, sovereignty, power etc. are all understood through the auspices of western centric theories of International Relations. The rise of Islamism/Political Islam, can be said to be one of the major catalysts to this critique. The mainstream theories are embedded in the secular intellectual tradition of the West. Therefore, unable to put into consideration issues such as the resurgence of Islam. The reason being, religion (in this case Islam) is considered irrelevant. Hence, making the theories unsuitable to understanding the dynamics pertaining to Islam and events in the Muslim world. Events such as the Islamic revolution, Muslim Brotherhood, Islamist militias such as al-Qaeda and the Islamic State (ISIS). It is therefore in the light of this, that this study seeks to contribute to the post-western debate by looking at concepts of state sovereignty, war and peace from an Islamic perspective. And ultimately, by proposing Islam as a theory to understanding events in the Muslim world.

ÖZ: Uluslararası İlişkiler disiplini içinde, disiplinin kapsamlı doğasına ilişkin büyüyen bir tartışma vardır. Amitav Acharya gibi Batılı olmayan bilim adamları, Uluslararası İlişkiler disiplininin batılı olmayan diğer teorileri dikkate almadığını iddia ettiler. Bunun, disiplinin kapsayıcılığını sınırladığına inanıyorlardı. Hakim ana akım teoriler, dünya çapında batılı olmayan karmaşık sorunları açıklamakta yetersiz kalıyor. Bunun nedeni, teorilerin Euro-Amerikan dünya görüşüne dayanmasıdır. Devlet, egemenlik, güç vb. kavramların tümü, Batı merkezli Uluslararası İlişkiler teorilerinin himayesinde anlaşılmaktadır. İslamcılığın/Siyasal İslam'ın yükselişinin bu eleştirinin ana katalizörlerinden biri olduğu söylenebilir. Ana akım teoriler, Batı'nın seküler entelektüel geleneğine gömülüdür. Bu nedenle İslam'ın dirilişi gibi konuları dikkate almak mümkün değildir. Sebep, din (bu durumda İslam) alakasız olarak kabul edilir. Bu nedenle, teorileri İslam'a ilişkin dinamikleri ve İslam dünyasındaki olayları anlamak için uygunsuz hale getirmek. İslam devrimi, Müslüman Kardeşler, El Kaide gibi İslamcı milisler ve İslam Devleti (IŞİD) gibi olaylar. Bu nedenle, bu çalışma, devlet egemenliği, savaş ve barış kavramlarına İslami bir perspektiften bakarak Batı sonrası tartışmalara katkıda bulunmayı amaçlamaktadır. Ve nihayetinde, İslam dünyasındaki olayları anlamak için İslam'ı bir teori olarak önererek
Master of Arts in International Relations. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2021. Supervisor: Prof. Dr. Erol Kaymak
Keywords: Thesis Tez; Political Science and International Relations Department; Religion and politics; Islam; secular; International Relations; mainstream; Theory